2008
DOI: 10.1016/j.cub.2008.02.034
|View full text |Cite
|
Sign up to set email alerts
|

SCALLOPED Interacts with YORKIE, the Nuclear Effector of the Hippo Tumor-Suppressor Pathway in Drosophila

Abstract: In Drosophila, SCALLOPED (SD) belongs to a family of evolutionarily conserved proteins characterized by the presence of a TEA/ATTS DNA-binding domain [1, 2]. SD physically interacts with the product of the vestigial (vg) gene, where the dimer functions as a master gene controlling wing formation [3, 4]. The VG-SD dimer activates the transcription of several specific wing genes, including sd and vg themselves [5, 6]. The dimer drives cell-cycle progression by inducing expression of the dE2F1 transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
339
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(357 citation statements)
references
References 37 publications
13
339
0
2
Order By: Relevance
“…Subsequent biochemical studies showed that Wts directly phosphorylates and inhibits Yki (Dong et al, 2007). Scalloped (Sd), the homolog of mammalian TEAD family transcription factors, were found to be critical partners of Yki in the regulation of gene expression (Goulev et al, 2008;Wu et al, 2008;Zhang et al, 2008;Zhao et al, 2008;Zhang et al, 2009a). Several transcriptional targets of the Hippo pathway have been identified, including cyclin E, which directly promotes cell cycle progression and cell proliferation, and diap1, which inhibits apoptosis (Tapon et al, 2002;Jia et al, 2003;Udan et al, 2003;Wu et al, 2003;Lai et al, 2005).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent biochemical studies showed that Wts directly phosphorylates and inhibits Yki (Dong et al, 2007). Scalloped (Sd), the homolog of mammalian TEAD family transcription factors, were found to be critical partners of Yki in the regulation of gene expression (Goulev et al, 2008;Wu et al, 2008;Zhang et al, 2008;Zhao et al, 2008;Zhang et al, 2009a). Several transcriptional targets of the Hippo pathway have been identified, including cyclin E, which directly promotes cell cycle progression and cell proliferation, and diap1, which inhibits apoptosis (Tapon et al, 2002;Jia et al, 2003;Udan et al, 2003;Wu et al, 2003;Lai et al, 2005).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…Furthermore, Yki-Sd was shown to transcriptionally induce dMyc, a potent promoter of ribosome biogenesis and cell growth (Neto-Silva et al, 2010;Ziosi et al, 2010), which may mediate the cell competition phenomenon observed in tissues with imbalance of Hippo pathway activity. In addition, Yki induces E2F1 (Goulev et al, 2008), which may be involved in cell-autonomous regulation of cell proliferation; the EGFR ligands Vein, Keren, and Spitz (Zhang et al, 2009b;Ren et al, 2010); the Jak/Stat pathway ligands Unpaired1/2/3 (Upd1/2/3) (Karpowicz et al, 2010;Ren et al, 2010;Shaw et al, 2010;Staley and Irvine, 2010), which could mediate non-cell-autonomous function of the Hippo pathway; and the Hippo pathway genes Ex, Kibra, Crb, and Fj (Cho et al, 2006;Hamaratoglu et al, 2006;Genevet et al, 2009;Genevet et al, 2010), which may constitute a signal feedback loop.…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of Yki by Wts inhibits Yki nuclear localization, preventing it from acting on its growth-promoting and apoptosisinhibiting targets. Yorkie functions with the transcription factor Scalloped in the regulation of growth control [58][59][60] .…”
Section: Growth Control By Fat Pcp Regulatorsmentioning
confidence: 99%
“…These proteins suppress growth by the phosphorylation or cytosolic retention of the transcriptional coactivator Yorkie (Yki), which cannot bind to DNA directly (Huang et al, 2005). Yki interacts with a transcription factor Scalloped (Sd), which induces tissue overgrowth (Goulev et al, 2008;Wu et al, 2008;Zhang et al, 2008). The Wts-Hpo signaling factors are now considered as general regulators of organ size in both Drosophila and mammals (Reddy and Irvine, 2008;Halder and Johnson, 2010;Pan, 2010;Zhao et al, 2010).…”
Section: Fig 2 Drosophila Adult Leg Phenotypes Ofmentioning
confidence: 99%